Marketing for the bank executive - Berry, Leonard L.; Capaldini, L. A. (New York : Petrocelli Books, 1974)
Marketing for the Bank Executive has been prepared specifically for people who are not particularly knowledgeable in marketing but who would like to become more knowledgeable. The is meant to introduce the essence of marketing, its philosophy, overall structure, and key concepts, in an orderly, logical, understandable way.
Includes index
Bibliography: p. 272-277.
usc 31/05/2017
Loans
Keywords: Bank marketing